United States Work Projects Administration records - United States. Work Projects Administration; United States. Works Progress Administration; Federal Writers' Project; Writers' Program (U.S.)
Series A. includes correspondence, memoranda, speeches, essays, scripts, plays, oral testimony in the form of life histories, folklore material, field reports, notes, transcripts of documents, inventories, lists, statements, instructions, surveys, critical appraisals, administrative records, graphs, drawings, maps, and other records. Subjects include production of American Guide-books which were intended to encourage travel to various states to bolster the economy during the Great Depression, rural and urban folklore, customs of social and ethnic groups, and African Americans both slaves and ex-slaves. Folklorists include Benjamin Albert Botkin and John A. Lomax. Authors include Nelson Algren, Sterling Brown, Jack Conroy, and Richard Wright. Correspondents include Henry Alsberg, Merle Colby, George Cronin, Joseph Gaer, Reed Harris, and Claire Laning.
Series B includes correspondence, memoranda, reports, surveys, notes, data sheets, lists, instructional manuals, personnel records, transcripts of documents, newspaper articles, catalog entries, newspaper articles, and index cards. Subjects include church and religious activity in Washington, D.C., boards, commissions, and departments of the nation's capitol, and Mormons in Utah.
Series C includes speeches, reports, publications, financial material, personnel forms, procedural and instructional manuals, press releases, newsletters, bulletins, promotional material, statistical data, graphs, illustrations, photographs, and related records. Documents the social welfare programs of the Depression era including the U.S. Federal Emergency Relief Administration, the U.S. Work Projects Administration, and private organizations including American Public Welfare Association, Chamber of Commerce of the United States of America, Community Chests and Councils of America, and Family Welfare Association.
Series D consists of card files from an indexing project of the slave narratives.
Microfilm edition of slave narratives also available in the Library of Congress Microforms Reading Room, no. 974 (E); cataloged in record 83145588.
Life histories and corollary documents assembled by the Folklore Project with the Federal Writer's effort, 1936-1940, also available through the Library of Congress Web site under the title, American life histories : manuscripts from the Federal Writers' Project, 1936-1940.
Slave narratives available through the Library of Congress Web site under the title, Born in slavery: slave narratives from the Federal Writers' Project, 1936-1938.
Microfilm edition of inventory of Mormon diaries available
Microfilm edition of containers A693-705 available
Microfilm edition of containers A917-A932 available
Keywords: Algren, Nelson, -- 1909-1981.; Alsberg, Henry G. -- 1881-1970.; Alsberg, Henry G. -- 1881-1970 -- Correspondence; Botkin, Benjamin Albert, -- 1901-1975.; Brown, Sterling Allen, -- 1901-1989.; Colby, Merle, -- 1902-1969 -- Correspondence; Conroy, Jack, -- 1898-1990.; Cronin, George -- Correspondence; Gaer, Joseph, -- 1897-1969 -- Correspondence; Harris, Reed -- Correspondence; Laning, Claire -- Correspondence; Lomax, John A. -- 1867-1948.; Wright, Richard, -- 1908-1960.; United States. -- Federal Emergency Relief Administration; American Public Welfare Association; Chamber of Commerce of the United States of America; Community Chests and Councils of America; Family Welfare Association of America; African Americans; Depressions -- 1929.; Ethnic groups -- United States; Slavery -- United States; Urban folklore -- United States; Folklore -- United States; Mormons -- Utah; United States -- Description and travel; United States -- Economic conditions -- 1918-1945.; United States -- Ethnic relations; United States -- Social life and customs; Washington (D.C.) -- Politics and government; Washington (D.C.) -- Religion